Punching shear capacity of nonprestressed UHPFRC flat Plates: Evaluation of existing methods. (1st April 2023) - Cakmak, Furkan; Menkulasi, Fatmir; Dogu, Mehmet
Highlights: An experimental database of 64 punching critical UHPC plates was compiled. Correlations between the shear stress at failure and various parameters were discussed. 13 prediction methodologies were evaluated. The average ratio and COV of measured to predicted punching capacity ranged from 0.50-2.42, and 36%-58%, respectively. The methodology presented in the K-UHPC code appears to be most appropriate for design. Abstract: An experimental database of 64 nonprestressed ultra high performance fiber reinforced concrete (UHPFRC) flat plates reported to fail in punching shear was generated and characterized. The selected plates featured round, end-hooked, and deformed steel fibers. All plates have uniform thickness with no shear reinforcement. Trends and correlations between the shear stress at failure and various parameters were investigated. The shear stress at failure was on average four times higher than the shear stress corresponding with the first crack. There was a notable positive correlation between nonprestressed flexural reinforcement ratio and shear stress at failure. Plate ductility at punching shear failure varied significantly. A total of 13 prediction methodologies were considered for final evaluation, 8 of which were developed for UHPFRC, 4 were developed for fiber reinforced concrete (FRC), and 1 was developed for high performance fiber reinforced concrete (HPFRC). The predictive performance of the various prediction models was evaluated using common statistical indicators, as well as a demerit point classification model. The average ratio of measured to predicted punching shear capacity ranged from 0.50 to 2.42. The corresponding coefficients of variation (COVs) ranged from 36% to 58%. Only five out of 13 prediction methodologies underpredicted, on average, the nominal punching shear capacity. The large COV suggests the need for more accurate prediction methods that capture fundamental phenomena observed during tests while being informed by parameters that are practical to obtain. Guidelines for casting methods that produce the desired distribution of fibers are essential in yielding a more predictable plate response.